Biogrouting with microbial-induced carbonate precipitation (MICP) for improving the physical and mechanical properties of granular soils potential liquefaction - Nur Ayu Diana; Ria Asih Aryani Soemitro; Januarti Jaya Ekaputri; Trihanyndio Rendy Satrya; Dwa Desa Warnana (MethodsX, 2025)
Biogrouting, a method to enhance soil properties using microorganisms and mechanical techniques, has shown great potential for soil improvement. Most studies focus on small sand columns in labs, but recent tests used 0.5 m plastic boxes filled with sand stabilized with microorganisms and fly ash. The experiments, conducted over 30 days, applied injection and infusion methods with microbial fluids, maintaining groundwater levels to simulate field conditions. Mechanical properties were analyzed through unconfined compressive strength (UCS) tests on extracted samples. Researchers also assessed calcium carbonate distribution and shear strength. Results showed water saturation significantly influenced vertical stress (qu), while UCS correlated with the permeability of sand containing varying calcium carbonate levels. Bacillus safensis, a resilient bacterium used in this process, can withstand extreme conditions. After completing its task, it enters a dormant state and reactivates when needed. The bacteria produce calcium carbonate by binding calcium with enzymes, which cements soil particles, enhancing strength and stability. • Testing enzymes on microbes and natural soil • Installation settings for drip tools using infusion • Soil resistance testing after stabilization using UCS